Implementasi Konsep A3 Untuk Mengurangi Reject Proses Assembly - Rahman Soesilo (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
The A3 concept is one of the Toyota tools to propose problem-solving solutions. A3 provides status reports of ongoing activities. This research applies A3 concept to solve reject problem in plastic company assembling process. The reject rate in the assembly process is 15.6%. The implementation stage of A3 concept is identification of problem, targeting, root cause, goal setting, countermeasure, implementation plan, action and follow up. The A3 concept is in line with the Plan-Do-Check-Act (PDCA) process improvement cycle. The results show that using the concept of A3 can reduce the reject Assembly effectively and precisely.